(untitled) (Eurasian Journal of Religious Studies, 2024)
The article is devoted to the study of the history of the struggle of the Orthodox in Kazakhstan for the objects of worship in the 1920-1940s during the period of renewal schism in the Russian Orthodox Church (ROC). The methodological basis of the work is the civilizational approach, the principle of historicism, the authors use a complex of general scientific and special historical methods of research. As sources, the normative documents on state-church relations and the materials of the business of local authorities and management were used. Documents from the regional archives of the Republic of Kazakhstan are analyzed. The task of the study is to study and identify the regional features of the renewal movement in Kazakhstan in the first decades of Soviet power and the position of ordinary believers in the years of the split. The Orthodox confession was one of the numerous in the republic, occupying the second place after Islam.The schismatic movement in the Russian Orthodox Church reached the regions of Kazakhstan and manifested itself in the confrontation between the “tihonovists” and the “renewalists”. This struggle was most acute in the cities of Kazakhstan, where the church clergy switched to the side of the Renovationists. In the provinces and districts of the republic, the renewal did not find wide support among the Orthodox population. Most of the common people remained loyal to the ideas of Patriarch Tikhon. Archival sources testify to the political component of the schism and the formal support of the "renewalists" by local Soviet authorities in the 1920s. But in the 1930s, the anti-religious policy of the Soviet state led to the closure of religious sites, regardless of the communities’ affiliation with any particular direction of the Renovationist schism. Keywords: Church Schism, Soviet power, Kazakhstan, religious communities, archival sources.